Pilot testing of enhanced sorbents for calcium looping with cement production - Erans moreno, María; Jeremias, Michal; lyzheng@alum.imr.ac.cn; Yao, Joseph G.; Blamey, John; Manovic, Vasilije; Fennell, Paul S.; Anthony, Ben (Cranfield University, 2018)
Raw data from pilot plant experiments depicted in "Pilot testing of enhanced sorbents for calcium looping with cement production"
Keywords: 'calcium looping'; 'pilot testing'; 'Carbon Capture Engineering (excl. Sequestration)'